Writing Dublin: Joyce, Bloomsday and Tourism in the Irish Capital - Lemos, Márcia (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
In his undeniable masterpiece Ulysses (1922), Joyce blurred the limits between fact and fiction from the very beginning as he announced his desire to provide an extremely detailed picture of Dublin, so complete, in fact, that the city could be reconstructed out of his book, if necessary. An exile on the Continent (Trieste, Zurich and Paris) from a very early age, Joyce always wrote of Ireland and his tribute to the Irish capital in Ulysses inspired a very original and unique annual celebration. It is called Bloomsday - after Leopold Bloom, the protagonist of Ulysses - and it is commemorated on June 16, mirroring the novel‟s action set on June 16, 1904. The purpose of this paper is twofold: to analyse how Joyce‟s modernist Dublin odyssey shares some traits with travel writing and to understand the importance of Ulysses and its annual celebration to boost literary tourism in Ireland.